Titanium porous body and method for manufacturing titanium porous body

By turning the molded body after drying to volatilize the organic binder from the upper side, the method addresses compression resistance issues in titanium porous bodies, ensuring high yield and performance in PEM type water electrolysis devices.

JP2024178464AInactive Publication Date: 2024-12-24TOHO TITANIUM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024172740
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-01
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing titanium porous bodies used in PEM type water electrolysis devices suffer from poor compression resistance, leading to issues with maintaining thickness and shape under compressive forces, which affects air permeability and liquid permeability, and result in low manufacturing yields due to surface wrinkles when high sintering temperatures are used.

Method used

A method involving sequential drying and binder removal steps, where the molded body is turned over after drying to ensure the organic binder is volatilized from the upper side, preventing surface defects and enhancing compression resistance while maintaining air and liquid permeability.

Benefits of technology

The method produces titanium porous bodies with excellent compression resistance and required air and liquid permeability, achieving high manufacturing yields and suitable for use in PEM type water electrolysis devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178464000001
    Figure 2024178464000001
Patent Text Reader

Abstract

To provide a titanium porous body that has a relatively large surface area and excellent compression resistance, and can exert required air permeability or liquid permeability, and a method for manufacturing a titanium porous body in which such a titanium porous body can be manufactured at a relatively high yield.SOLUTION: A titanium porous body is sheet-like, has a thickness t of 0.50 mm or less, a projection area onto a flat surface of a surface of 28000 mm2 or more, and an irreversible deformation amount after pressurizing at 100 MPa of 1.0% or less, in which air permeability P (μm / Pa S) satisfies the relation of P≥I with an index value I, and the index value I is expressed by I=1.6×(1 / t)1.3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet-shaped porous titanium body and a method for producing a porous titanium body. [Background technology]

[0002] Porous titanium produced by, for example, sintering titanium powder has fine pores that provide air or liquid permeability and electrical conductivity, and also has high corrosion resistance due to the formation of a passive film on the surface.

[0003] Porous titanium with such properties is being considered for use in porous transport layers (PTLs) in polymer electrolyte membrane (PEM)-type water electrolysis equipment, which are in environments where corrosion may occur. In particular, hydrogen produced in PEM-type water electrolysis equipment using electricity derived from renewable energy is called "green hydrogen," and is attracting great expectations in recent years as the movement toward a decarbonized society accelerates.

[0004] In this regard, Patent Document 1 discloses a method for producing a porous titanium sintered body, comprising: a slurry preparation step of mixing at least one of titanium powder and titanium hydride powder with an organic binder, a foaming agent, a plasticizer, water, and optionally a surfactant to prepare a slurry; a molding step of applying the slurry onto a first support to form a molded body; a foaming step of heating and drying the molded body to foam it, thereby preparing a foamed molded body; a degreasing step of heating and degreasing the foamed molded body separated from the first support and placed on a second support; a first sintering step of heating the degreased foamed molded body in a non-oxidizing atmosphere to prepare a primary sintered body having electrical conductivity; and a second sintering step of sintering the primary sintered body in a non-oxidizing atmosphere at a temperature higher than that in the first sintering step to produce a porous titanium sintered body. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-102701 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the above-mentioned water electrolysis apparatus, from the viewpoint of miniaturization of the apparatus, a thin sheet-like titanium porous body having excellent compression resistance is sometimes required. This is because a titanium porous body with poor compression resistance will not be able to maintain the required thickness or shape against the compressive force that may act when incorporated inside an apparatus such as a PEM-type water electrolysis apparatus, and there is a concern that the air permeability or liquid permeability will decrease.

[0007] One way to obtain a porous titanium body with high compression resistance is to increase the sintering temperature during production. However, when producing a porous titanium body with a relatively large surface area (projected area on a flat surface), if the heating temperature during sintering is increased to a certain degree, wrinkles will appear on the surface of the sintered porous titanium body, making it more likely to produce defective products and reducing the production yield.

[0008] Patent Document 1 makes no consideration whatsoever about improving the compression resistance of the titanium porous body.

[0009] An object of the present invention is to provide a porous titanium body which has a relatively large surface area, is excellent in compression resistance and exhibits the required air and liquid permeability, and a method for producing such a porous titanium body which can produce such a porous titanium body with a relatively high yield. [Means for solving the problem]

[0010] As a result of intensive research, the inventors have devised a method of drying the paste containing titanium powder, removing the binder from the resulting molded body, and sintering the titanium powder in sequence, by turning the molded body over after drying and removing the binder. This allows the organic binder that accumulates on the lower mounting surface side in the paste during drying to be located on the upper side when the molded body is turned over after drying, and to volatilize well during debinding. As a result, even if the molded body is heated at a relatively high temperature during sintering, the occurrence of defects such as wrinkles on the surface of the sintered titanium porous body can be suppressed, and the yield is improved. In addition, the titanium porous body manufactured in this way has excellent compression resistance and relatively high air permeability or liquid permeability. The organic binder accumulates on the lower mounting surface side in the paste during drying because the organic solvent located on the upper side opposite to the mounting surface side volatilizes preferentially during drying, and as drying progresses, the organic binder on the upper side dissolves and accumulates in the organic solvent on the lower side, which is less likely to volatilize. If the binder is then removed without turning the green body over, the organic binder on the lower side will remain and prevent the titanium powder from coming into close proximity or contact during sintering, resulting in the formation of somewhat large holes, which is thought to make it difficult to improve compression resistance.

[0011] The porous titanium body of the present invention is in the form of a sheet, has a thickness t of 0.50 mm or less, and a projected area of ​​the surface on a flat surface of 28,000 mm. 2 or more, the amount of irreversible deformation after pressurization at 100 MPa is 1.0% or less, the air permeability P (μm / Pa S) and the index value I satisfy the relationship P≧I, and the index value I satisfies I=1.6×(1 / t) 1.3 It is expressed as follows.

[0012] The titanium porous body preferably has a titanium content of 97% by mass or more and an oxygen content of 0.9% by mass or more and 2.0% by mass or less.

[0013] The titanium porous body has a surface projected area of ​​600,000 mm 2 It is preferable that:

[0014] The above-mentioned porous titanium body preferably has a thickness t of 0.04 mm or more.

[0015] The above-mentioned porous titanium body preferably has a ten-point average roughness Rz of at least one surface of 9 μm or less.

[0016] The method for producing a titanium porous body of the present invention is a method for producing a sheet-like titanium porous body, and includes the steps of: a drying step in which a paste containing titanium powder, an organic binder and an organic solvent, but not containing water or a foaming agent, is heated on a mounting surface to dry it, thereby obtaining a sheet-like molded body; a binder removal step in which the molded body is heated on the mounting surface in an orientation reversed from the orientation on the mounting surface in the drying step, thereby volatilizing the organic binder in the molded body; and a sintering step in which the molded body after the binder removal step is heated and the titanium powder in the molded body is sintered, the sheet-like porous body having a thickness of 0.50 mm or less and a projected area on a surface plane of 28,000 mm. 2 The above-mentioned porous titanium body is produced.

[0017] In the above manufacturing method, it is preferable to use, as the titanium powder, a pulverized powder having an average particle size D50 of 10 μm or more and 45 μm or less.

[0018] In the drying step, the paste is preferably heated to a temperature of 80° C. or more and 150° C. or less in an oxygen-containing atmosphere.

[0019] In the binder removal step, the compact is preferably heated to a temperature of 320° C. or more and 450° C. or less in an oxygen-containing atmosphere.

[0020] In the sintering step, the molded body is preferably heated in a reduced pressure atmosphere or an inert gas atmosphere.

[0021] In the sintering step, the molded body is preferably heated to a temperature of 750°C to 1000°C. Effect of the Invention

[0022] The porous titanium body of the present invention has a relatively large surface area, is excellent in compression resistance, and exhibits the required air and liquid permeability. According to the method for producing a porous titanium body of the present invention, such a porous titanium body can be produced with a relatively high yield. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the present invention will be described in detail. The titanium porous body according to one embodiment of the present invention is in the form of a sheet having a thickness t of 0.50 mm or less, and a projected area (apparent area in plan view) of 28,000 mm when the surface is projected onto a plane. 2 This porous titanium body has an irreversible deformation of 1.0% or less after being pressurized at 100 MPa, and the air permeability P (μm / Pa·S) satisfies the relationship P≧I with the index value I, so it has excellent compression resistance and can exhibit the required air and liquid permeability. The above index value I depends on the thickness t (mm), and is expressed as I=1.6×(1 / t) 1.3 It is expressed as:

[0024] To manufacture such a titanium porous body, for example, a step of drying a paste containing titanium powder can be carried out, followed by a step of debinding the resulting molded body and a step of sintering the titanium powder. In the drying step, the paste is heated and dried on a mounting surface to obtain a sheet-like molded body. In the manufacturing method of the embodiment, in the subsequent debinding step, the molded body is heated on the mounting surface in an orientation that is inverted from the orientation on the mounting surface in the drying step.

[0025] The inventors conducted various studies and came to the following conjecture. That is, when the paste is heated on the mounting surface in the drying process, as mentioned above, much of the organic binder in the paste migrates to the lower mounting surface, and a large amount of the organic binder may be present on the lower side of the molded body obtained in the drying process. If the binder removal process is carried out in this orientation, the organic binder on the lower side of the molded body may not be sufficiently removed and may remain. If the molded body is then heated in the sintering process, the titanium porous body is likely to become a defective product due to the formation of wrinkles or ridges on its surface caused by the evaporation of the organic binder in the sintering process. This is particularly true for porous titanium bodies with a surface projection area of ​​28,000 mm2. 2 This problem becomes evident when manufacturing a large porous titanium body of the above size. In this case, the organic binder remaining on the lower side during sintering prevents the titanium powder from bonding together, which makes it easy for relatively large holes to form there, and the compression resistance of the porous titanium body cannot be increased significantly.

[0026] In contrast, as described above, by turning the molded body over after the drying process, the organic binder that was located on the lower side of the molded body after the drying process is located on the upper side (i.e., the side opposite to the mounting surface side), and is more likely to volatilize in the subsequent binder removal process. As a result, the generation of defective products is suppressed in the sintering process, and the manufacturing yield can be improved. In addition, since the organic binder is favorably volatilized in the binder removal process, the formation of relatively large holes (pores) due to the remaining organic binder is suppressed in the sintering process. In addition, the organic binder is favorably separated from the molded body to be subjected to the sintering process, and the particles of the titanium powder are appropriately arranged in the molded body and sintered, so that the required air permeability or liquid permeability can be secured. As a result, a titanium porous body that is excellent in compression resistance and can exhibit the required air permeability or liquid permeability even when compressed is obtained.

[0027] (Porous titanium) The titanium porous body is made of titanium. If it is made of titanium, a titanium porous body having high electrical conductivity at a certain relative density can be obtained. The titanium content of the titanium porous body is preferably 97% by mass or more, and more preferably 98% by mass or more. The upper limit of the titanium content is not limited to this, but may be, for example, 99.8% by mass or less, or 99% by mass or less. This titanium content means the purity of titanium taking into account not only metal components but also impurities of gas components such as oxygen. Therefore, the titanium content can be calculated by subtracting the total content of impurity components including metal components and gas components from 100% by mass.

[0028] The titanium porous body may contain Fe as an impurity, and the Fe content may be, for example, 0.25 mass% or less. The titanium porous body may also contain Ni, Cr, Al, Cu, Zn, and Sn as unavoidable impurities resulting from the manufacturing process. It is preferable that each of the contents of Ni, Cr, Al, Cu, Zn, and Sn is less than 0.10 mass%, and that the total content of these elements is less than 0.30 mass%.

[0029] The oxygen content of the titanium porous body is not particularly limited, but may be 0.9% by mass or more and 2.0% by mass or less. When the drying step and / or binder removal step are carried out in an oxygen-containing atmosphere as in the manufacturing method described below, the oxygen content of the titanium porous body may increase to some extent. The oxygen content can be measured by inert gas fusion-infrared absorption method.

[0030] The titanium porous body may have a purity equivalent to pure titanium class 1 to 4, typically class 1 or 2, of JIS H 4600 (2012), excluding the oxygen content.

[0031] The thickness t of the sheet-like titanium porous body is 0.50 mm or less, and may be 0.04 mm or more. For example, a porous transport layer of a PEM type water electrolysis device may require a titanium porous body with such a thickness t. If the thickness t is too large, the PEM type water electrolysis device may become large. The thickness t of the titanium porous body is, for example, 0.40 mm or less, 0.35 mm or less, 0.30 mm or less, 0.25 mm or less, or 0.20 mm or less, and may be 0.04 mm or more, or 0.08 mm or more.

[0032] The thickness t is determined by measuring a total of five points, four points on the periphery and one point in the center, of the titanium porous body using a digital thickness gauge with a flat gauge having a Φ10 mm probe and a measurement accuracy of 0.001 to 0.01 mm, such as a Mitutoyo digital thickness gauge (model number 547-321), and averaging these measurements. When the sheet-like titanium porous body is rectangular in plan view, the four peripheral points are the four corners.

[0033] The projected surface area of ​​the sheet-shaped porous titanium body in plan view is 28,000 mm 2 For example, 600,000 mm 2 The following may be used. A porous titanium body with a relatively large surface projected area can be cut and used as needed, and is suitable for mass production. On the other hand, when an attempt is made to manufacture a porous titanium body with a large surface projected area, there is a tendency for a large number of defective products to be produced, but according to the embodiment described here, the occurrence of such defective products can be suppressed. The projected area here means the area of ​​the surface of the porous titanium body projected onto a plane.

[0034] The term "sheet-like" in relation to the titanium porous body means a plate-like or foil-like body having a thickness smaller than the dimensions in a plan view. The shape of the titanium porous body in a plan view is not particularly limited, but may be a square shape, or a rectangular shape, a rhombus, or other polygonal shape with an aspect ratio of 1:1 to 1:3. The corners of the polygonal titanium porous body may be chamfered.

[0035] The titanium porous body is formed by bonding titanium powder particles together, and has a three-dimensional mesh structure in which pores are formed between the bonded titanium powder particles. As an example, the titanium porous body may have a skeleton with a three-dimensional mesh structure like titanium sponge. Note that titanium porous bodies manufactured using titanium fibers tend to have a three-dimensional mesh structure like nonwoven fabric. In many cases, the inside of the skeleton of the titanium porous body, which is formed by bonding titanium powder particles together, is solid, not hollow.

[0036] When the porous titanium body is compressed in its thickness direction by applying a pressure of 100 MPa for 3 minutes and then unloaded twice, the amount of irreversible deformation, which is the ratio of change in thickness before and after the operation, is 1.0% or less.

[0037] As a result, when the titanium porous body is incorporated inside a device such as a PEM water electrolysis device, a certain degree of thickness and shape is maintained when a compressive force is applied, and the required air and liquid permeability can be exhibited. The amount of irreversible deformation is preferably 1.0% or less. The amount of irreversible deformation may be, for example, 0.6% or less, and may be, for example, 0.5% or less. The smaller the amount of irreversible deformation, the better, so the lower limit is not particularly limited and can be set appropriately depending on the purpose.

[0038] More specifically, the amount of irreversible deformation Dc is a value calculated from the thickness T1 of the porous titanium body before a pressure of 100 MPa is applied and the thickness T2 of the porous titanium body after the pressure is applied and then unloaded, using the formula: Dc = (1 - T2 / T1) x 100. In order to measure the amount of irreversible deformation Dc, the thickness T1 of a square sample (projected area 20 mm x 20 mm) of the titanium porous body in plan view is measured in advance. Then, the sample is sandwiched between the flat surfaces of two flat plates or the like in the thickness direction, and the flat surfaces are displaced in a direction that brings them closer to each other, so that a pressure of 100 MPa is applied to the surface of the sample in the thickness direction evenly for 3 minutes. The displacement speed at this time can be constant at 0.1 mm / min. After applying the pressure, the pressure is released. This operation of applying and releasing the pressure is repeated, and the operation is performed twice in total. Then, the thickness T2 of the sample taken out from between the flat surfaces is measured. Here, various compression test devices and other devices capable of applying pressure to the sample in this way can be used. To measure the thicknesses T1 and T2 of the sample, the thickness is measured at one point at the center of gravity of the sample in plan view. This measurement is performed on five different samples, and the average value is adopted as the amount of irreversible deformation.

[0039] A porous titanium body with a relatively high air permeability P can be said to have good air permeability or liquid permeability. However, the air permeability P of a porous titanium body can vary depending on its thickness. Therefore, here, the air permeability or liquid permeability of a porous titanium body is evaluated by comparing the air permeability P of the porous titanium body with an index value I that depends on the thickness t (mm). The index value I is calculated using the formula: I=1.6×(1 / t) 1.3 It is a value expressed as:

[0040] Specifically, the porous titanium body of this embodiment has an air permeability P that satisfies the relationship P≧I with the above index value I. Such a porous titanium body can exhibit good air and liquid permeability, particularly in a PEM-type water electrolysis device.

[0041] The air permeability P (μm / Pa S) is measured according to the Gurley tester method, but here the volume of air passed through the titanium porous body is 300 mL. Specifically, using a Gurley densometer conforming to ISO 5635-5, such as Toyo Seiki Seisakusho's Gurley densometer (product number: G-B3C), the measurement hole diameter is set to Φ6 mm, the air volume is set to 300 mL, and the time (s) required for the air to pass through is measured. The ISO air permeability (μm / Pa S) thus obtained is taken as the air permeability P.

[0042] The ten-point average roughness Rz of at least one surface of the titanium porous body is preferably 9 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. The ten-point average roughness Rz of the surface is measured, for example, using a Mitutoyo SJ-210 in accordance with JIS B0601 (2001).

[0043] The titanium porous body is particularly suitable for use as a porous transport layer in a PEM-type water electrolysis device. The PEM-type water electrolysis device may include an anode and a cathode, an electrolyte membrane such as a perfluorocarbon sulfonic acid membrane disposed between the anode and the cathode and having electrode catalyst layers of a platinum group metal or the like provided on both sides, and a porous transport layer disposed between each electrode catalyst layer of the electrolyte membrane and the anode or the cathode.

[0044] In a PEM water electrolysis device, when water is supplied to the anode and a voltage is applied, the water moves through the porous transport layer on the anode side and reaches the electrode catalyst layer, where it is decomposed into oxygen and protons (H + The protons move from the anode to the cathode through the electrolyte membrane on the anode side, obtain electrons at the electrode catalyst layer on the cathode side, and generate hydrogen on the cathode side. Meanwhile, oxygen moves through the porous transport layer to the discharge flow path and is discharged outside the device.

[0045] In such a PEM-type water electrolysis device, the space in which the porous transport layer is disposed, particularly on the anode side, is subject to strong acidic and strong oxidation conditions, but a titanium porous body having high corrosion resistance can be used satisfactorily as a porous transport layer in such an extremely severe environment. Note that in the titanium porous body of this embodiment, a large number of fine pores are formed on at least one surface, and a surface with a small ten-point average roughness Rz can be realized, which may prevent damage to the electrolyte membrane when the surface side is pressed against the electrolyte membrane in a PEM-type water electrolysis device.

[0046] In addition to the PEM-type water electrolysis devices mentioned above, the use of titanium porous bodies is also being considered for organic electrolysis synthesis using PEM-type reactors. In such devices, electrolysis is carried out by passing protons through a proton exchange membrane. The titanium porous bodies described here may also be well suited for organic electrolysis synthesis using PEM-type reactors, and are considered to be usable as a porous transport layer (PTL) on the anode side of electrolysis devices that use proton exchange membranes.

[0047] (Manufacturing method) The above-mentioned titanium porous body can be manufactured, for example, by carrying out the following steps in this order: paste preparation, paste application, drying, binder removal, and sintering. However, if the paste has already been prepared and obtained, or if the paste has been applied in sheet form, the paste preparation and paste application steps may be omitted.

[0048] First, in a paste preparation step, a paste containing titanium powder, an organic binder, and an organic solvent is prepared.

[0049] Here, the average particle size D50 of the titanium powder contained in the paste can be 10 μm or more and 45 μm or less. The average particle size D50 of the titanium powder may be 10 μm or more and 30 μm or less, or 10 μm or more and 20 μm or less. This allows the use of relatively inexpensive titanium powder, suppressing increases in production costs, and facilitating the handling of the titanium powder. When titanium powder with a small average particle size D50 is used, the surface of the sheet-shaped titanium porous body tends to be smooth. Furthermore, if the titanium porous body is produced by adopting the production conditions described here, it is possible to produce a titanium porous body with a small amount of irreversible deformation while ensuring the required air permeability or liquid permeability. The average particle size D50 means the particle size at which the cumulative distribution on a volume basis is 50% in the particle size distribution obtained by the laser diffraction scattering method.

[0050] The titanium powder is preferably one with high purity, and pure titanium powder can be used. The titanium powder may have a titanium content of 99% by mass or more. The titanium powder may be a crushed powder, a spherical powder such as atomized powder, or any other powder. As the titanium powder, titanium hydride powder obtained by hydrogenating and crushing a titanium raw material such as sponge titanium can also be used. In this case, the hydrogen content of the titanium hydride powder is preferably 5% by mass or less. In addition, when using titanium hydride powder, a dehydrogenation treatment may be performed in a temperature range of 500°C or more and 650°C or less in a reduced pressure atmosphere such as a vacuum between the binder removal step and the sintering step described below. In addition, hydrogenated and dehydrogenated titanium powder (so-called HDH powder) obtained by dehydrogenating the above-mentioned titanium hydride powder can also be used.

[0051] In addition, various organic binders can be appropriately selected and used for the paste, and examples of such organic binders include methyl cellulose, polyvinyl alcohol, ethyl cellulose, acrylic, and polyvinyl butyral. Organic binders that exhibit hydrophobicity are preferable. However, they are not limited to those listed here. The organic solvent is alcohol (ethanol, isopropanol, terpineol, butyl carbitol, etc.). As an example, the organic binder may be polyvinyl butyral and the organic solvent may be isopropyl alcohol. The paste may further contain a plasticizer (glycerin, ethylene glycol, etc.) and a surfactant (alkylbenzene sulfonate, etc.).

[0052] The paste does not contain water as a solvent. It is preferable that the paste does not further contain a foaming agent. This is to suppress the aggregation of titanium powder in the paste due to the difference in drying behavior between the organic solvent and water during drying when the paste contains water, and the occurrence of pinholes on the surface of the titanium porous body. Furthermore, when the paste does not contain a foaming agent, large local voids due to foaming of the foaming agent are not formed in the titanium porous body. As a result, the titanium porous body is likely to have a smooth surface and is less likely to crack during handling. Therefore, a foaming process that generates bubbles in the paste is not performed here. It is sufficient that the paste does not contain water as a solvent, and the inclusion of water that may be unintentionally mixed into the paste due to moisture absorption or the like is permitted.

[0053] The paste can be prepared by mixing the titanium powder, organic binder, organic solvent, and the like as described above, using, for example, a mixer with an agitator, a rotary mixer, a triple roll mill, etc. At this time, the mixture may be pulverized using a vibration mill, a bead mill, or other pulverizing mixer, etc.

[0054] In the paste application step, the paste is applied relatively thinly onto the mounting surface of a substrate or the like. A release layer may be provided on the substrate in advance. In this case, the paste is applied onto the substrate via the release layer. When a release layer is provided on the substrate, it becomes easier to separate the molded body obtained by drying the paste from the substrate after the drying step.

[0055] The substrate is preferably a resin substrate, which is relatively inexpensive. In addition, the resin substrate has the advantage of being flexible and easy to handle. Specific materials for the resin substrate include polyesters such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate), and polyvinyls such as polyethylene, polypropylene, polystyrene, and polyvinyl alcohol. Among these, PET is preferable because it is inexpensive and the molded body can be easily separated from the substrate after the drying process.

[0056] It is optional to provide a release layer on the substrate, but when a release layer is provided, a silicone coating or the like can be used as the release layer. For example, a release layer can be provided on the substrate by selecting a substrate on which such a material has been applied in advance, such as Therapeel (registered trademark) manufactured by Toray Industries, Inc. By providing a release layer on the substrate, it becomes possible to easily separate the thin sheet-like molded body obtained after the drying process from the substrate.

[0057] In the drying step, the paste is dried on the mounting surface, for example, in an oven or a dryer, etc. This causes the organic solvent in the paste to evaporate, and a sheet-like molded body is obtained on the substrate.

[0058] The heating temperature during drying can be 80°C or higher and 150°C or lower. The heating temperature during drying can be 100°C or higher and 140°C or lower. By drying the paste at a temperature within this range, it is possible to complete the drying in a relatively short time while suppressing boiling of components such as organic solvents in the paste. The drying time is not particularly limited and may be appropriately determined, and can be, for example, 5 minutes or longer and 300 minutes or shorter. It is preferable to perform the drying in an oxygen-containing atmosphere, for example, in the air atmosphere. This can suppress an increase in manufacturing costs.

[0059] When the drying step is completed, the molded body obtained by drying the paste is separated from the mounting surface by peeling or the like, and the molded body is turned over, and then the binder removal step is performed. In other words, the turning over of the molded body here means turning the surface of the molded body that faced the lower mounting surface side in the drying step over to the upper side in the binder removal step, and turning the surface that faced the upper side in the drying step over to the lower mounting surface side in the binder removal step.

[0060] In the drying process, the organic binder may be biased toward the lower mounting surface side where the organic solvent in the paste is less likely to volatilize, but by turning the molded body over, the organic binder is located on the upper side in the binder removal process and volatilizes well. This makes it possible to suppress the generation of defective products after the sintering process described below, in which the molded body is heated at a relatively high temperature.

[0061] In the drying process and the binder removal process, the same substrate can be used as a member for placing the paste or the molded body, but different substrates can also be used. In this way, the placement surface in the drying process and the placement surface in the binder removal process do not necessarily coincide with each other.

[0062] Next, in the binder removal step, the molded body is heated in a furnace to volatilize and remove the organic binder in the molded body. At this time, by turning the molded body over as described above, the organic binder located on the upper side of the molded body can be effectively volatilized, and the organic binder remaining after the binder removal step is suppressed.

[0063] In the binder removal process, for example, the molded body is preferably heated to a temperature of 320°C or more and 450°C or less, or 360°C or more and 400°C or less. This makes it possible to remove the organic binder while suppressing sintering of the titanium powder due to heating. In this way, the appropriate position of each titanium powder in the molded body can be maintained. The heating time is not particularly limited, but may be 3 hours or more and 12 hours or less. The atmosphere during heating is preferably an oxygen-containing atmosphere such as air atmosphere. It is presumed that when an oxygen-containing atmosphere is used, the cost increase can be suppressed and an oxide film grows well on the surface of the titanium powder.

[0064] Thereafter, the compact that has been subjected to the binder removal process is subjected to a sintering process to sinter the titanium powder in the compact. In the sintering process, the compact is heated to a temperature of 750°C to 1000°C, preferably 775°C to 950°C. In the sintering process, the compact may be heated to the above temperature for 1 hour or more and 4 hours or less. The sintering atmosphere may be, for example, 1.0×10 -2 The atmosphere may be a vacuum or reduced pressure atmosphere of less than Pa, or an inert gas atmosphere of Ar or He.

[0065] By carrying out the binder removal step in an oxygen-containing atmosphere and then carrying out the sintering step in a reduced pressure atmosphere or an inert gas atmosphere, the oxygen in the oxide film that has grown on the surface of the titanium powder in the binder removal step is incorporated into the titanium powder in the sintering step, strengthening the sintered porous titanium body, and thus obtaining a porous titanium body with excellent compression resistance. Note that if the sintering step is also carried out in an oxygen-containing atmosphere, the oxygen in the atmosphere is also incorporated into the titanium powder in the sintering step, which may result in an excessive oxygen content.

[0066] After the sintering process, a titanium porous body is obtained. As mentioned above, this titanium porous body has high compression resistance and can exhibit the required air and liquid permeability. Here, the thickness is 0.50 mm or less, and the projected area of ​​the surface on a flat surface is 28,000 mm. 2 The porous titanium body is manufactured as described above. In order to obtain such dimensions, the application area and thickness of the paste in the paste application step can be adjusted. EXAMPLES

[0067] Next, a titanium porous body according to the present invention was produced as a prototype and its effects were confirmed, which will be described below, however, the description here is merely for illustrative purposes and is not intended to be limiting.

[0068] A paste was prepared by mixing titanium powder (HDH powder) having an average particle size D50 shown in Table 1 and a titanium content of 99 mass% or more with polyvinyl butyral as an organic binder and isopropyl alcohol as an organic solvent. The paste prepared in this manner does not contain water or a foaming agent.

[0069] The paste was applied in sheet form onto the mounting surface of a PET resin substrate and dried to form a compact. This compact was then debindered and sintered to produce a porous titanium body having a rectangular shape in plan view (aspect ratio within the range of 1:1 to 1:3). Drying was performed by heating the paste to 120°C in an air atmosphere. Debindering was performed by heating the compact to 380°C in an air atmosphere. Sintering was performed in a vacuum atmosphere (1×10 -2 The heating temperature is as shown in Table 1.

[0070] In Examples 1 to 7, after drying, the molded body was peeled off from the resin substrate, and placed upside down on the mounting surface of a graphite setter, and then debinding was performed. In Comparative Examples 1 to 3, after drying, the molded body was peeled off from the resin substrate, but was not turned over, and was placed on the mounting surface of a graphite setter in the same orientation as during drying, and debinding was performed.

[0071] As a result, after sintering, titanium porous bodies with good flat surfaces were obtained in Examples 1 to 7 and Comparative Example 2, whereas in Comparative Examples 1 and 3, wrinkles protruding from the surface were formed on the surface of the titanium porous bodies, resulting in defective products. From this, it was found that in order to manufacture titanium porous bodies with a large projected area on a flat surface as in Examples 1 to 7, the occurrence of defective products can be suppressed by turning the bodies over after drying and before removing the binder. The projected areas and thicknesses shown in Table 1 were each measured according to the method described above.

[0072] For each of the titanium porous bodies of Examples 1 to 7, the amount of irreversible deformation, as well as the air permeability P and index value I were measured or calculated using the methods described above. The results are shown in Table 1. All of the titanium porous bodies of Examples 1 to 7 had a titanium content of 97% by mass or more and an oxygen content in the range of 0.9% by mass or more and 2.0% by mass or less.

[0073] As shown in Table 1, all of the titanium porous bodies of Examples 1 to 7 had excellent compression resistance because the irreversible deformation amount was sufficiently small, and P≧I, and had the required air permeability or liquid permeability. This is thought to be due to the good volatilization of the organic binder in the binder removal process and the high heating temperature during sintering. In particular, in Examples 2 and 3, in which the heating temperature during sintering was further increased, and in Examples 6 and 7, in which titanium powder with a small average particle size D50 was used, the amount of irreversible deformation of the titanium porous body was smaller, and in some cases, such as Examples 6 to 7, it was substantially zero. In Examples 6 to 7, the results were below the lower limit of the measuring device, so they were marked as "less than 0.4%." In Comparative Example 2, the titanium porous body had a small projected surface area.

[0074] [Table 1]

[0075] The above suggests that this invention may make it possible to produce, with high yield, a porous titanium body which has a relatively large surface area, excellent compression resistance, and is capable of exhibiting the required air and liquid permeability.

Claims

1. A sheet-shaped porous titanium body, The thickness t is 0.50 mm or less, and the projected area of ​​the surface on the plane is 28,000 mm 2 That's all. The amount of irreversible deformation after pressure application at 100 MPa is 1.0% or less, The air permeability P (μm / Pa·S) and the index value I satisfy the relationship P≧I, and the index value I is I=1.6×(1 / t) 1.3 The titanium porous body is represented by the formula:

2. 2. The titanium porous body according to claim 1, having a titanium content of 97% by mass or more and an oxygen content of 0.9% by mass or more and 2.0% by mass or less.

3. The projected area of ​​the surface is 600,000 mm 2 3. The titanium porous body according to claim 1 or 2, wherein:

4. 3. The titanium porous body according to claim 1, having a thickness t of 0.04 mm or more.

5. 3. The titanium porous body according to claim 1, wherein at least one surface has a ten-point average roughness Rz of 9 μm or less.

6. A method for producing a sheet-shaped porous titanium body, comprising the steps of: a drying step of heating and drying a paste containing titanium powder, an organic binder, and an organic solvent, but not containing water or a foaming agent, on a mounting surface to obtain a sheet-like molded body; a binder removal step of heating the molded body on a mounting surface in an inverted orientation relative to the orientation on the mounting surface in the drying step to volatilize the organic binder in the molded body; a sintering step of heating the compact after the binder removal step to sinter the titanium powder in the compact; Including, The thickness is 0.50 mm or less and the projected area on the surface is 28,000 mm 2 A method for producing a porous titanium body, comprising the steps of: producing the porous titanium body described above;

7. The method for producing a porous titanium body according to claim 6, wherein the titanium powder used is a crushed powder having an average particle size D50 of 10 μm or more and 45 μm or less.

8. 8. The method for producing a porous titanium body according to claim 6 or 7, wherein in the drying step, the paste is heated to a temperature of 80° C. or more and 150° C. or less in an oxygen-containing atmosphere.

9. 8. The method for producing a porous titanium body according to claim 6 or 7, wherein in the binder removal step, the formed body is heated to a temperature of 320° C. or more and 450° C. or less in an oxygen-containing atmosphere.

10. The method for producing a porous titanium body according to claim 6 or 7, wherein in the sintering step, the molded body is heated in a reduced pressure atmosphere or an inert gas atmosphere.

11. The method for producing a porous titanium body according to claim 6 or 7, wherein the molded body is heated to 750°C to 1000°C in the sintering step.

Citation Information

Patent Citations

  • Method for manufacturing porous sintered body of titanium and apparatus for manufacturing porous sintered body of titanium

    JP2009102701A